2006
DOI: 10.1158/1535-7163.mct-05-0548
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal prostaglandin E synthase-1 regulates human glioma cell growth via prostaglandin E2–dependent activation of type II protein kinase A

Abstract: Dysregulation of enzymes involved in prostaglandin biosynthesis plays a critical role in influencing the biological behavior and clinical outcome of several tumors. In human gliomas, overexpression of cyclooxygenase-2 has been linked to increased aggressiveness and poor prognosis. In contrast, the role of prostaglandin E synthase in influencing the biological behavior of human gliomas has not been established. We report that constitutive expression of the microsomal prostaglandin E synthase-1 (mPGES-1) is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 41 publications
4
32
0
1
Order By: Relevance
“…33 The same discrepancy can be observed in cell culture. mPGES-1 could namely promote the growth of a human glioma cell line 34 through PGE 2 extracellular pathway, whereas we showed that it was a proapoptotic enzyme in human brain tumor primary cultures through the activation of Bax by intracellular PGE 2 and subsequent caspase activity. 8 We confirmed that this discrepancy was linked to PGE 2 localization, as the pharmacological sequestration of PGE 2 was sufficient to induce apoptosis.…”
Section: Discussionmentioning
confidence: 65%
“…33 The same discrepancy can be observed in cell culture. mPGES-1 could namely promote the growth of a human glioma cell line 34 through PGE 2 extracellular pathway, whereas we showed that it was a proapoptotic enzyme in human brain tumor primary cultures through the activation of Bax by intracellular PGE 2 and subsequent caspase activity. 8 We confirmed that this discrepancy was linked to PGE 2 localization, as the pharmacological sequestration of PGE 2 was sufficient to induce apoptosis.…”
Section: Discussionmentioning
confidence: 65%
“…Gathering this data from our study and the others mentioned, we have reason to believe that mPGES1 is expressed and produced in the five glioma cell lines A-172, U-251MG, U-87MG, U-138MG, and T-98G. Payner et al (2006) demonstrated that blocking mPGES1 activity and expression inhibited the release of PGE 2 and decreased cellular proliferation. This implies that mPGES1 can regulate glioma growth through a PGE 2 -dependent pathway, making mPGES1 a valuable target for treatments.…”
Section: The Confirmed Presence Of the Pgd 2 Synthesis Pathwaysupporting
confidence: 72%
“…However, they did not detect mPGES1 in U-138MG (Payner et al, 2006). Using immunohistochemistry, we observed a strong staining of mPGES1 in U-87MG, U-251MG and A172.…”
Section: The Confirmed Presence Of the Pgd 2 Synthesis Pathwaymentioning
confidence: 55%
“…An increased expression of mPGES-1 in the tissues of patients of brain cancer has also been reported from another group in a subset of human glioblastoma multiforme (GBM) tumors, the most common form of adult brain cancer, astrocytoma and high-risk neuroblastoma. [45][46][47] An activated COX/mPGES-1/PGE 2 pathway has been identified in 11q-deleted neuroblastoma with high expression of mPGES-1, and elevated levels of PGE 2 as compared with low-risk tumors. Analysis of expression cohorts revealed a worse outcome for high-risk patients (INSS stage 4) with high mPGES-1 expression.…”
Section: Role Of Mpges-1 In Brain Cancermentioning
confidence: 99%